Phage derived lytic peptides, a secret weapon against Acinetobacter baumannii—An in silico approach - Nandy, Abhishek; Yadav, Ruchi; Singh, Aditi (Frontiers in Medicine, 2022)
Acinetobacter baumannii is a bacterial pathogen that is commonly associated with hospital-acquired illnesses. Antimicrobial drug resistance in A. baumannii includes several penicillin classes, first and second-generation cephalosporins, cephamycins, most aminoglycosides, chloramphenicol, and tetracyclines. The recent rise in multidrug-resistant A. baumannii strains has resulted in an increase in pneumoniae associated with ventilators, urinary tract infections associated with the catheter, and bloodstream infections, all of which have increased complications in treatment, cost of treatment, and death. Small compounds known as antimicrobial peptides (AMPs) are known to have damaging effects on pathogenic bacteria. To determine their antimicrobial activity, AMPs are created from proteins acquired from various sources and evaluated in vitro. In the last phase of lytic cycle, bacteriophages release hydrolytic enzymes called endolysins that cleave the host's cell wall. Due to their superior potency and specificity compared to antibiotics, lysins are used as antibacterial agents. In the present study, different types of endolysin from phages of Acinetobacter baumannii were selected based on an extensive literature survey. From the PhaLP database, the sequences of the selected lysins were retrieved in FASTA format and antimicrobial peptides were found among them. With the help of available bioinformatic tools, the anti-biofilm property, anti-fungal property, cell-penetrating property and cellular toxicity of the antimicrobial peptides were determined. Out of the fourteen antimicrobial peptides found from the eight selected endolysins of Acinetobacter baumannii specific phage, eight of them has anti-biofilm property, nine of them has anti-fungal property, five of them has cell-penetrating property and all of them are non-toxic.